Characteristics of patients with rheumatic heart disease in a national referral hospital in Indonesia (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND Rheumatic heart disease (RHD) is one of the most common cardiovascular problems in Indonesia. Comprehensive data regarding patient characteristics are critical in planning optimal treatment strategies to relieve the burden of RHD. This study aimed to describe the clinical and echocardiographic characteristics of patients across several types of valvular lesions in RHD in the Indonesian population. METHODS This retrospective study was performed between January 2016 and June 2019 at the National Cardiovascular Center Harapan Kita, Jakarta, Indonesia. The study population comprised all patients with significant valve disease aged ≥18 years. Patient characteristics and echocardiographic parameters were collected retrospectively from medical records and hospital information systems. Patients were classified into several groups based on etiologies of valve disease. RESULTS Of 5,482 patients with significant valve lesions, 2,333 (42.6%) were RHD patients. They were predominantly female (64.1%) and younger (mean [standard deviation] age 42.61 [12.01] years). Atrial fibrillation (AF) was the most frequent rhythm disorder observed in RHD (65.4%). Isolated mitral stenosis was the most common valve lesion in RHD patients (46.5%). Most patients with RHD had preserved left ventricular (LV) ejection fraction. Half of the patients with mitral stenosis had reduced right ventricular (RV) contractility (tricuspid annular plane systolic excursion <17 mm). CONCLUSIONS Isolated mitral stenosis was the most observed condition of valve lesions in RHD. Characteristics of RHD patients in this study were predominantly female, younger age, had preserved LV function, reduced RV function, and high prevalence of AF.